Diagnostic and prognostic value of long-axis strain and myocardial contraction fraction using standard cardiovascular MR imaging in patients with nonischemic dilated cardiomyopathies - Arenja, Nisha; Riffel, Johannes; Fritz, Thomas; André, Florian; Siepen, Fabian aus dem; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Katus, Hugo; Friedrich, Matthias; Buß, Sebastian Johannes (Radiology, 2017)
Purpose To assess the utility of established functional markers versus two additional functional markers derived from standard cardiovascular magnetic resonance (MR) images for their incremental diagnostic and prognostic information in patients with nonischemic dilated cardiomyopathy (NIDCM). Materials and Methods Approval was obtained from the local ethics committee. MR images from 453 patients with NIDCM and 150 healthy control subjects were included between 2005 and 2013 and were analyzed retrospectively. Myocardial contraction fraction (MCF) was calculated by dividing left ventricular (LV) stroke volume by LV myocardial volume, and long-axis strain (LAS) was calculated from the distances between the epicardial border of the LV apex and the midpoint of a line connecting the origins of the mitral valve leaflets at end systole and end diastole. Receiver operating characteristic curve, Kaplan-Meier method, Cox regression, and classification and regression tree (CART) analyses were performed for diagnostic and prognostic performances. Results LAS (area under the receiver operating characteristic curve [AUC] = 0.93, P < .001) and MCF (AUC = 0.92, P < .001) can be used to discriminate patients with NIDCM from age- and sex-matched control subjects. A total of 97 patients reached the combined end point during a median follow-up of 4.8 years. In multivariate Cox regression analysis, only LV ejection fraction (EF) and LAS independently indicated the combined end point (hazard ratio = 2.8 and 1.9, respectively; P < .001 for both). In a risk stratification approach with classification and regression tree analysis, combined LV EF and LAS cutoff values were used to stratify patients into three risk groups (log-rank test, P < .001). Conclusion Cardiovascular MR-derived MCF and LAS serve as reliable diagnostic and prognostic markers in patients with NIDCM. LAS, as a marker for longitudinal contractile function, is an independent parameter for outcome and offers incremental information beyond LV EF and the presence of myocardial fibrosis